PERLINDUNGAN HUKUM BAGI DEBITUR TERHADAP KREDITURYANG TIDAK MELAKSANAKANKEWAJIBANPENGHAPUSAN (ROYA) JAMINAN FIDUSIA DI PT PEGADAIAN SYARIAH CABANG SUBRANTAS PEKANBARU - Hikmah, Hidayatul; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Every object guaranteed by the Fiduciary Guarantee must be registered with theFiduciary Registration Office. The purpose of fiduciary registration is to guaranteelegal certainty and provide legal protection for the parties concerned. Fiduciaryregistration should end with the deletion (roya) of fiduciary guarantees as in Article 16paragraph (2) of Government Regulation Number 21 of 2015 concerning Proceduresfor Registration of Fiduciary Guarantees and Costs for Making Fiduciary GuaranteeActs. As long as the fiduciary recipient has not notified him of the abolition of thefiduciary guarantee and the issuance of the fiduciary guarantee certificate is no longervalid, the object which is the object of the fiduciary guarantee has not been erased andremains attached as a debt guarantee. in accordance with Article 7 paragraph (2) ofGovernment Regulation Number 21 of 2015 concerning Procedures for Registration ofFiduciary Guarantees and Costs for Making Fiduciary Deed Guarantees, the relevantfiduciary guarantees cannot be re-registered. The problems examined in this study are,how to carry out the elimination (roya) of Fiduciary Guarantee at PT. PegadaianSyari'ah Pekanbaru Subrantas Branch and how is the responsibility of PT. PegadaianSyari'ah Pekanbaru Subrantas Branch (creditor) to the debtor in terms of the removal(roya) of fiduciary collateral.The type of research that the author uses is juridical sociological researchapproach that emphasizes the legal aspects related to the subject matter to bediscussed, related to the reality that occurs in the field. In this case the authorsconducted research at PT. Pegadaian Syariah Subrantas Pekanbaru Branch. The dataused consists of primary data and secondary data. Technical data were collected byfield studies (interviews and questions and literature studies). Then analyzedqualitatively and make conclusions with deductive thinking methods.From the results of this study it can be concluded that there are two points thatcan be concluded. First, that the implementation of the obligation to delete (roya)Fiduciary Guarantee at PT. Pegadaian Syari'ah Pekanbaru Subrantas Branch has notbeen in accordance with applicable laws and government regulations. Second, that theresponsibilities that PT. pegadaian syari`ah Subrantas Pekanbaru Branch againstdebtors in the event of a problem in the future, namely the pawnshop in good faith willeradicate (roya) the fiduciary guarantee of the debtor by attaching their KTP, proof ofpayment and BPKB.Keywords: Fiduciary Collateral, Elimination (Roya) Fiduciary Collateral.